Salesian pedagogy of accompaniment in the social rehabilitation of minors - Bogdan Stańkowski (Multidisciplinary Journal of School Education, 2025)
Research objectives (aims) and problem(s): The aim of this article is to explore whether, and to what extent, the literature on the social rehabilitation of minors in the Salesian context addresses the issue of pedagogical accompaniment and to consider the direction which this accompaniment should take. The author seeks to answer three main questions: